Norway : Financial Sector Assessment Program-Technical Note-Insurance Sector Oversight. (IMF Staff Country Reports; Country Report, 2020)
The Norwegian insurance sector is well-capitalized. In recent years, the authorities have taken steps to recapitalize weak insurers and to boost capital for the overall industry. Risk-resilience has been strengthened by stronger retention of profits leading to accumulation of reserves, better risk management, and higher capital in the run-up to the implementation of the Solvency II regulatory regime.